2011
DOI: 10.1111/j.1464-410x.2011.10695.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of stone management in Australia

Abstract: What's known on the subject? and What does the study add? There is very little contemporary data regarding stone management in Australia. This study assesses the impact of technological advances on stone management practises, and raises questions as to why there is an increasing rate of intervention for stone disease in Australia. Knowledge of management trends as demonstrated in this paper give individual surgeons a guideline for contemporary practise in this country. OBJECTIVE To examine trends in the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 16 publications
(17 reference statements)
3
48
0
2
Order By: Relevance
“…Previous studies have also shown superior SFRs for ureteral compared to renal stones with SWL [8,10], but the small number of ureteral stones has frequently limited the applicability of such analyses. Although these findings do not, in isolation, identify SWL as the best available management strategy for ureteral stones, there remains no strong evidence, in the form of prospective randomised controlled trials, to demonstrate the superiority of ureteroscopy (URS) over SWL in managing such stones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown superior SFRs for ureteral compared to renal stones with SWL [8,10], but the small number of ureteral stones has frequently limited the applicability of such analyses. Although these findings do not, in isolation, identify SWL as the best available management strategy for ureteral stones, there remains no strong evidence, in the form of prospective randomised controlled trials, to demonstrate the superiority of ureteroscopy (URS) over SWL in managing such stones.…”
Section: Discussionmentioning
confidence: 99%
“…The European Association of Urology (EAU) guidelines recommend SWL as the first line management option for proximal ureteral stones <10mm, and an equivalent first line option to endourology for renal stones <20mm, proximal ureteral stones >10mm and distal ureteral stones <10mm [7]. In spite of this, reports indicate that the rate of SWL use has plateaued or decreased in recent years alongside a surge in the use of ureteroscopy with the holmium laser [8][9][10][11], and despite evidence suggesting similar success rates between management options [7]. The current evidence examining the use of SWL demonstrates wide variation in clinical outcomes, with overall stone free rates (SFRs) ranging from 40.2% to 96.8%, and is limited to studies reporting small cohorts or in which multiple models of SWL machine has been used [12].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, in the last few years, improved endoscopic surgical material and greater experience on the part of surgeons have led to an increase in endoscopic surgery rates. 6 The present work analyzed the evolution of the different treatments for lithiasis that has taken place at our hospital over the last 15 years.…”
Section: Palabras Clavementioning
confidence: 99%
“…La mayoría de las litiasis solo requieren tratamiento médico y/o expulsivo, siendo un escaso porcentaje el que requiere un tratamiento invasivo o quirúrgico. Actualmente los tratamientos invasivos de los que disponemos son por orden de uso la litotricia extracorpórea por ondas de choque (LEOC), la cirugía endoscópica (ureterorrenoscopia [URS], cirugía renal retrógrada [CRR]), la cirugía percutánea (NLP) y la cirugía abierta (CA), incluyendo en este grupo la cirugía laparoscópica y robótica 5,6 . De estas modalidades de tratamiento la LEOC es la más empleada por el tamaño de las litiasis y su localización, por su rapidez, menor morbilidad, posibilidad de realización con sedación y de llevarla a cabo ambulatoriamente, lo que repercute en una mayor aceptación por parte del paciente de esta modalidad de tratamiento 7 .…”
Section: Introductionunclassified
“…De estas modalidades de tratamiento la LEOC es la más empleada por el tamaño de las litiasis y su localización, por su rapidez, menor morbilidad, posibilidad de realización con sedación y de llevarla a cabo ambulatoriamente, lo que repercute en una mayor aceptación por parte del paciente de esta modalidad de tratamiento 7 . Sin embargo, en los últimos años la mejora en el material quirúrgico endoscó-pico y la mayor experiencia de los cirujanos ha hecho que se observe un incremento en las tasas de cirugía endoscópica 6 . En el siguiente trabajo vamos a ver la evolución de los diferentes tratamientos de la litiasis que se ha producido en nuestro hospital en los últimos 15 años.…”
Section: Introductionunclassified